Switching-table and space vector modulation direct torque control of permanent magnet synchronous motor drives simulation - Said, Mohamed Azmi (2009)
Direct torque control (DTC) is considered as the best alternative for permanent magnet synchronous (PMSM) drives. Classic switching-table based DTC has high torque and flux ripple due to the implementation of hysteresis control. Switching frequency can be made constant by replacing hysteresis control with space vector PWM (SVM) and requires mathematical modification on SVM input. Propotional+integral control and reference flux vector calculation (RFVC) is used to improve the torque response, flux and torque ripple. These scheme still utilizing similar torque and flux estimator as introduced in classic DTC. Propotional+integral control DTC performed better in term of torque step response whilst RFVC torque and flux ripple are the best among these three schemes.